A corpus-based analysis of scientific TED Talks: Explaining cancer-related topics to non-experts. (April 2019) - Mattiello, Elisa
Highlights: The language that TEDsters use is effective but also accessible to non-experts. The techniques used range from periphrasis to simile, metaphor, and hyperbole. Figurative language is often used to enhance the comprehensibility of the talks. Frequent collocations evoke the metaphor CANCER IS ENEMY (to fight). TED Talks can also help psycho-oncology experts to support cancer sufferers.